Handheld electrochemical device for the determination of the strength of garlic - Ngamchuea, K; Hurst, P; Batchelor-McAuley, C; Compton, R (Elsevier, 2016)
A handheld electrochemical sensor has been demonstrated for the quantification of the strength of garlic. The device is based on the enhanced voltammetric response in the presence of organosulfur compounds extracted from garlic. Convenient and disposable platinum screen-printed electrodes are employed. All measurements and data analyses are performed within the device. A linear response of the voltammetric peak current enhancement as a function of garlic concentration was observed, indicating the ability of the device to be applied to garlic samples of any strength. Importantly, this portable sensor can be used by non-scientifically skilled personnel and does not require expensive laboratory equipment. It is thus suitable for application in the food industry.